The right to independent living for adult people with disabilities and emancipatory opportunities in Italy - Decembrotto, Luca (Education Sciences & Society - Open Access, 2019)
The present contribution proposes some reflections stemming from the right to independent living for adult people with disabilities and from the level of emancipation, lingering on some specific housing projects available in Italy. The examined data comes from a nationwide research carried out by the University of Bologna, which focused on which residential services are available today for adult people with disabilities, taking also in account how stimulation extends towards the dwellers in choosing autonomous housing.